Association of metabolic syndrome with sensory gating deficits in patients with chronic schizophrenia. (July 2015) - Micoulaud-Franchi, Jean-Arthur; Faugere, Mélanie; Boyer, Laurent; Cermolacce, Michel; Richieri, Raphaëlle; Faget, Catherine; Philip, Pierre; Vion-Dury, Jean; Lancon, Christophe
Highlights: Sensory gating deficit can be assessed with the P50 suppression index in schizophrenia. Patients with metabolic syndrome exhibit abnormal P50 suppression index. Metabolic syndrome is associated with sensory gating deficit in schizophrenia. Abstract: Metabolic syndrome is more prevalent in schizophrenia than in the general population and is associated with an increased rate of morbidity. It has been associated with cognitive impairments in schizophrenia, which are a core deficit in patients with chronic schizophrenia. Sensory gating deficit is also a core deficit in schizophrenia. The principal objective of this study was to investigate the relationship between sensory gating deficit and metabolic syndrome in patients with schizophrenia, after adjusting for key confounding factors. We hypothesized that patients with metabolic syndrome exhibit a higher rate of sensory gating deficit compared to those without metabolic syndrome. This study investigated sensory gating with the auditory event-related potential method by measuring P50 amplitude changes in a double click conditioning-testing procedure in 51 patients with schizophrenia. Patients with metabolic syndrome ( n  = 14) had a higher rate of sensory gating deficit (P50 suppression <50%) ( p  < 0.001) compared to those without metabolic syndrome ( n  = 37). This result remained significant ( B  = 2.94, Wald = 8.32, p  = 0.004) after taking into account 5 potential confounding factors (age, gender, duration of disorder, Fagerström test, presence of clozapine or olanzapine). In patients without metabolic syndrome, sensory gating deficit was linked to a poorer attentional performance (rho = −0.371, p  = 0.05). In patients with metabolic syndrome, sensory gating deficit was linked to poorer memory performance (rho = −0.635, p  = 0.02). These findings suggest that metabolic syndrome may be linked to sensory gating deficit in patients with schizophrenia and that the relationship between neurocognitive function and sensory gating deficit could be affected by the metabolic status of the patients. Further studies are needed to address the causal relationship between sensory gating deficit related to schizophrenia, cognitive impairments and metabolic syndrome.